Current Strategy of Fetal Therapy II: Invasive Fetal Interventions - Nawapun, Katika; Phithakwatchara, Nisarat; Panchalee, Tacharee; Viboonchart, Sommai; Mongkolchat, Nadda; Wataganara, Tuangsit (Journal of Fetal Medicine, 2017)
Invasive fetal intervention provides potential benefits to the fetus, but risks to the mother and the fetus are not negligible. Large congenital pulmonary airway malformation (CPAM) may cause fetal hydrops. Shunt placement in macrocystic type or steroids administration in microcystic type CPAM have been reported to reverse the hydrops in a small case series. In selected cases of fetal congenital diaphragmatic hernia (CDH), tracheal plugging may prevent egress of the lung fluid, promote lung proliferation, and maturation of pulmonary vasculature, which favor survival in isolated right-sided CDH fetuses or those with a lung-to-head ratio of ≤1.0. Fetoscopic cystoscopy with laser fulguration of the posterior urethral valve improves the 6-month survival and renal function. A randomized controlled trial to validate the real benefits of this procedure is still underway. Laser photocoagulation of anastomosing vessels is the standard of care for severe mid-trimester twin-to-twin transfusion syndrome. The principle of equipoise is likely to be reached on the issue of optimal treatment for Quintero stage I disease. Open fetal surgery has been offered in some cases of fetal tumor and myelomeningocele (MMC). Alternatively, endoscopic approach is being investigated to minimize procedure-related maternal morbidity. Only when procedure-related complications are properly prevented and managed, it is expected that invasive therapeutic innovation will then improve perinatal outcomes of selected fetal conditions.
Keywords: Fetal therapy; In-utero intervention; Twin-to-twin transfusion syndrome; Congenital diaphragmatic hernia; Posterior urethral valve; Myelomeningocele